Water-Soluble Sacrificial Layer of Sr3Al2O6 for the Synthesis of Free-Standing Doped Ceria and Strontium Titanate - Simone Sanna; Olga Krymskaya; Antonello Tebano (Applied Sciences)
Epitaxial layers of water-soluble Sr3Al2O6 were fabricated as sacrificial layers on SrTiO3 (100) single-crystal substrates using the Pulsed Laser Deposition technique. This approach envisages the possibility of developing a new generation of micro-Solid Oxide Fuel Cells and micro-Solid Oxide Electrochemical Cells for portable energy conversion and storage devices. The sacrificial layer technique offers a pathway to engineering free-standing membranes of electrolytes, cathodes, and anodes with total thicknesses on the order of a few nanometers. Furthermore, the ability to etch the SAO sacrificial layer and transfer ultra-thin oxide films from single-crystal substrates to silicon-based circuits opens possibilities for creating a novel class of mixed electronic and ionic devices with unexplored potential. In this work, we report the growth mechanism and structural characterization of the SAO sacrificial layer. Epitaxial samarium-doped ceria films, grown on SrTiO3 substrates using Sr3Al2O6 as a buffer layer, were successfully transferred onto silicon wafers. This demonstration highlights the potential of the sacrificial layer method for integrating high-quality oxide thin films into advanced device architectures, bridging the gap between oxide materials and silicon-based technologies.